Psychological factors associated with lifestyle in Venezuelan university students - Espina-Romero, Lorena C.; Guerrero-Alcedo, Jesús M.; Marreros Tananta, Jaime (Revista de Ciencias Sociales, 2023)
College brings emotional, cognitive, and physiological changes in students, along with academic stress that can affect their lifestyle and health. The present study aimed to determine the influence of psychological factors associated with the lifestyles of Venezuelan higher education students. This research was a quantitative, non-experimental study that analyzed the relationship between lifestyles, life satisfaction and sense of coherence in 843 students at the Simon Bolivar University in Venezuela. An accidental non-probabilistic sampling was used and standardized questionnaires were applied to collect data. The findings showed that sense of coherence is a significant predictor of lifestyle (β= .47; p=.002). The overall model presents acceptable fit indices, explaining 37% of the total variance of lifestyle. This study shows that the sense of coherence and life satisfaction influence healthy lifestyles in Venezuelan higher education students; moreover, the sense of coherence is an important predictor of these lifestyles. Promoting these psychological variables as facilitating resources for healthy behaviors can increase the health and well-being of students.